Isolation and development - Quamrul Ashraf; Oded Galor; Omer Ozak (Brown University, Department of Economics, 2009)
This paper exploits cross-country variation in the degree of geographical isolation, prior to the advent of sea-faring and airborne transportation technologies, to examine its impact on the course of economic development across the globe. The empirical investigation establishes that prehistoric geographical isolation has generated a persistent beneficial effect on the process of development and contributed to the contemporary variation in the standard of living across countries.
Keywords: O10; F15; N7; 330; Growth; Development; Isolation; Agglomeration; Globalization; Wirtschaftsgeographie; Internationale Zusammenarbeit; Entwicklung; Wirtschaftsgeschichte; Vorgeschichte; Welt